Unravelling the Cu and Ce effects in MnO2-based catalysts for low-temperature CO oxidation - Blinov, Egor D.; Kulchakovskaya, Ekaterina V.; Sokovikov, Nikolai A.; Svetlichnyi, Valerii A.; Kulinich, Sergei A.; Vodyankina, Olga V. (Nanomaterials)
Cu-containing and Ce-modified OMS-2 catalysts were prepared at various calcination temperatures using the hydrothermal method and tested for low-temperature CO oxidation. The structure, chemical compositions, and physical-chemical properties of the catalysts were characterized using XRD, N2 physisorption, XRF, Raman spectroscopy, SEM, high-resolution TEM with EDX, TPR-H2, and XPS. The incorporation of Cu into the Ce-OMS-2 sample facilitated the transformation of pyrolusite into cryptomelane, as confirmed by Raman spectroscopy data. In the light-off mode, the Cu/Ce-OMS-2-300 and Cu/OMS-2 samples exhibited higher activity in low-temperature CO oxidation (T90 = 115 and 121 ◦C, respectively) compared to sample Cu/Ce-OMS-2-450. After a long-run stability test, the Cu/Ce-OMS-X samples demonstrated excellent performance: the T80 increased by 16% and 7% for the samples calcined at 300 ◦C and 450 ◦C, respectively, while the T80 for the Cu/OMS-2 increased by 40%. The Cu/OMS-2 and Cu/Ce-OMS-2-300 samples were found to have an increased content of nanodispersed copper sites on their surfaces. These copper sites contributed to the formation of the Cu2+-O-Mn4+ interface, which is responsible for the CO oxidation. The presence of Ce3+ in the catalyst was found to increase its stability in the presence of water vapor due to the higher reoxidation ability in comparison with Ce-free sample Cu/OMS-2.